(untitled) (Research, Society and Development, 2021)
With the existing competitiveness in the market, the search of organizations for efficiency requires processes of excellence, which excel in quality in business performance. With this, companies tirelessly seek intellectual capital, which can be a differentiating subject in this scenario. In view of this, the work aims to show achievements and challenges that self-managing teams bring to organizations, describing the environment conducive to the development of self-managing teams. This was a descriptive and exploratory case study. As for the approach, it was enhanced from the quantitative and qualitative method, in which a semi-structured questionnaire was used in data collection, applied to a consulting company in People Management (GP), which has been working for twenty years to insert high-performance employees in the companies of the market, such as forming self-manageable teams in their workforce. The questionnaire was applied in the GP sector, which consisted of eight employees. As a result, it demonstrated the importance of having autonomous teams within the companies but immersed in several difficulties in coping with work activities as well as: lack of empowerment of team members; insecurity in the decision-making process; difficulty of management in delegation in decisions. In contrast to the various challenges faced, there are the numerous achievements of the team that outlast the perspectives of the objectives previously outlined by the company, in achieving organizational growth and development.